E.T.A. Hoffmann e a questão ótica - Korfmann, Michael (Contingentia, 2008)
In Hoffmann’s tales, visual references and optical devices play an important role as thmatic ans structural components. This article will analyze this subject ina a historical context where the social differentiation and the optica media result in a questioning of observation and perspective. Hoffmann’s writing may therefore be conveived, at least patially, through his position towards visibility. This paper will first provide a general look at the interrelations between Hoffmann’s texts and certain painting styles and then take a closer look at "The Sandmann" as a keywork for romantic perpectivism.